2021
DOI: 10.1177/20503121211012254
|View full text |Cite
|
Sign up to set email alerts
|

Do psychiatric disorders affect patient reported outcomes and clinical outcomes post total hip and knee arthroplasty?

Abstract: Introduction: The purpose of this study is to evaluate the role of major psychiatric illness on patient outcomes after total joint arthroplasty. Methods: Patients with a diagnosis of a major psychiatric disorder undergoing total joint arthroplasty were retrospectively matched one-to-one with a cohort without such a diagnosis. Major psychiatric disorder in the registry was identified by diagnosis of anxiety, mood, or a psychotic disorder. Primary outcome of interest included perioperative Western Ontario and Mc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
9
0
2
Order By: Relevance
“…However, there was no difference in reported functional status during these time periods [74, 75]. In studies grouping patients with any psychiatric illness for analysis, there were no differences reported in WOMAC or Patient-Reported Outcome Measure Information System scores compared with patients without mental disorders after 1 year of follow-up [48, 54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no difference in reported functional status during these time periods [74, 75]. In studies grouping patients with any psychiatric illness for analysis, there were no differences reported in WOMAC or Patient-Reported Outcome Measure Information System scores compared with patients without mental disorders after 1 year of follow-up [48, 54].…”
Section: Resultsmentioning
confidence: 99%
“…For the outcome measure of cost, the included studies only reported partial economic evaluations such as the total cost of hospitalization or reimbursement claims; thus, these relatively superficial analyses were deemed comparable in the quality of evidence they provided. Fifteen articles evaluated the association between perioperative complications and a diagnosed comorbid illness [11,14,15,26,42,45,46,48,59,60,70,78,83,84,95]. Eight articles reported on readmission rates after TJA [28,42,48,60,70,77,83,84].…”
Section: Primary and Secondary Study Outcomesmentioning
confidence: 99%
“…Assessing patient-reported resilience before arthroplasty may assist clinicians to identify those who are at risk of sub-optimal outcomes after arthroplasty, who are not identified using current methods. Current methods often focus on a formal diagnosis of depression or anxiety, use of psychoactive medications, use of generic quality of life outcome measures, or diagnosis-specific outcome measures [ 12 15 ]. Assessing resilience may be a more sensitive method of identifying those at risk of poor outcomes, as it considers how patients respond to adversity, rather than a narrow identification of specific diagnoses [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Встановлено, що обмеження функції та біль при ураженні кульшового суглобу більшою мірою пов'язані з особистісними та психологічними чинни-* © Шорніков А. В., Огоренко В. В., 2022 ками, неефективними копінг-стратегіями, ніж з патологічними та анатомічними чинниками [2]. Через це у пацієнтів з психічними розладами збільшується тривалість стаціонарного лікування при операціях з ендопротезування і вони частіше потребують тривалішої реабілітації [3]. Пацієнти з показаннями до ендопротезування суглобів мають більш високі показники клінічно значущих симптомів депресії до та після операції як порівняти із загальною популяцією, а операція призводить лише до помірного покращення тяжкості симптомів депресії та тривоги [4].…”
unclassified
“…Під первинним спостереженням перебувало 137 осіб з АНГСК та НПР, з яких 96 дійшли до кінця дослідження, решта вибули з дослідження через відмову. Це узгоджується з даними Kooner та співавт., які спостерігали показник втрати для подальшого спостереження близько 90 % за один рік [3]. Усі обстежені надали особисту письмову інформовану згоду на участь у дослідженні.…”
unclassified